Does the hazard rate for new plants vary between low- and high-tech industries? - Talat Mahmood (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1991)
Based on a longitudinal data base the hazard rate of over 12,000 newly established plants in U.S. manufacturing industry in 1976 are estimated and then compared between low and high-tech industries. It is found that the hazard rate differs across industries, and it also varies between low- and high-tech industries. The hazard rate in low-tech industries is reduced in the presence of scale economies, whereas the exposure to risk tends to be higher in high-tech industries. The influence of start-up size in reducing the hazard rate is apparently similar between low and high-tech industries, but its role is found to be more important in the high-technological industries. Market growth and R&D intensity exert no influence on the hazard rate in either the low- or high-tech industries. – – Für mehr als 12.000 Betriebe, die 1976 im verarbeitenden Gewerbe der USA neu gegründet wurden, wird anhand von Zeitreihen die Hazardrate geschatzt und zwischen Low- und High-Tech-Industrien verglichen. Es wurde festgestellt, daß sich die Hazardrate. der einzelnen Industrien unterscheidet und auch zwischen Low- und High-Tech-Industrien variiert. Die Hazardrate in den Low-Tech-Industrien verringert sich beim Vorhandensein von Größenvorteilen, wobei High-Tech-Industrien einem hoheren Risiko ausgesetzt sind. Der Einfluß der Anfangsgroße auf die Verminderung der Hazardrate ist anscheinend ahnlich zwischen Low- und High-Tech-Industrien, aber ihre Rolle ist in den High-Tech-Industrien viel wichtiger. Marktwachstum und F&E Intensitat üben keinen Einfluß auf die Hazardrate in den Low- und High-Tech- Industrien aus.
Keywords: 330